CHANGING CHILD-REARING PRACTICES AMONG YORUBA PARENTS IN IBADAN, NIGERIA (2014)
Yoruba child-rearing practices are predicated on a distinctive cultural value-system, marked by continuous changes. While an extensive literature has evaluated aspects of the practices in relation to child-development, family and educational studies, there has been little concentration on the shifting patterns. This study, therefore, ethnographically explored the changes in child-rearing practices among Yoruba parents in Ibadan, Nigeria, with a view to affirming how socio-economic transformative processes influenced modifications in child-rearing practices. Survey research design was adopted. Data were elicited through primary and secondary sources. 210 copies of a questionnaire were administered to 72 parents (purposively drawn among literate and illiterate parents engaged in formal and informal occupations), 63 children, 34 child-care workers and 41 teachers, purposively selected from five local government areas in Ibadan metropolis. In-depth interviews were conducted with 29 informants comprising 20 parents, three teachers, three child-care workers and three children. In addition, participant observation was held in 20 homes and direct observation of 30 family units. Quantitative data were analysed using descriptive statistics while qualitative data were content analysed. Changes in child-rearing practices in Ibadan occurred with regard to obedience, respect, morality, responsibility, enculturation and adoption of Yoruba as a medium of communication. Obedience, formerly characterised by stringent adherence, has been replaced with liberal models which were more dominant among elite parents, private child-care workers and schoolteachers. A mix of stringent and liberal patterns was confirmed by 74.2% respondents to be prevalent among some parents and public schoolteachers. Respect values instilled through normative practices have yielded ground to western greeting norms and conducts, as affirmed by 78.0% respondents to be largely reflected among elite children. Inculcation of moral values has predominantly shifted from enforcement of cultural norms, to higher reliance on religious precepts, as asserted by 80% of the respondents. Responsibility practices have transformed among elite parents, with their children mostly participating less in domestic activities. However, 82.8% of the respondents asserted some parents enforced children‘s engagement in domestic chores. Enculturation has been modified from parents‘ active participation with greater support from communal, extended and fosterage system, to lesser participation and measurable support. Teachers and child-care workers have, however, assumed central socialisation roles. In addition, 69.5% respondents affirmed more of children‘s enculturation process take place through the mass media, digital technologies and peer influence. The domestic pattern of adopting Yoruba as medium of communication is being displaced, more so among elite families where prevailingly English is the preferred language of interaction at home. This prevailing linguistic trend has the outcome of producing Yoruba children who are mostly incompetent in speaking, reading and writing both Yoruba and English, and are thereby culturally alienated. The socio-economic transformative processes resulting in increased literacy, acculturation of foreign norms, modifications in parents‘ occupational engagements and working structures, and imbalance in work and parenting responsibilities influenced the alterations. Socio-economic transformations have wrought both positive and culturally unfit changes in Yoruba child-rearing practices. Alternative measures of balancing work and parenting obligations would advance self-awareness and cultural grounding in Yoruba child-rearing practices.